Tumor marker analyses from the phase III, placebo-controlled, FASTACT-2 study of intercalated erlotinib with gemcitabine/platinum in the first-line treatment of advanced non-small-cell lung cancer - Mok T. (2017)
© 2016 The Authors. Objectives: The FASTACT-2 study of intercalated erlotinib with chemotherapy in Asian patients found that EGFR mutations were the main driver behind the significant progression-free survival (PFS) benefit noted in the overall population. Further exploratory biomarker analyses were conducted to provide additional insight. Materials and methods: This multicenter, randomized, placebo-controlled, double-blind, phase III study investigated intercalated first-line erlotinib or placebo with gemcitabine/platinum, followed by maintenance erlotinib or placebo, for patients with stage IIIB/IV non-small cell lung cancer (NSCLC). Provision of samples for biomarker analysis was encouraged but not mandatory. The following biomarkers were analyzed (in order of priority): EGFR mutation by cobas ® test, KRAS mutation by cobas ® KRAS test, HER2 by immunohistochemistry (IHC), HER3 by IHC, ERCC1 by IHC, EGFR gene copy number by fluorescence in-situ hybridization (FISH) and EGFR by IHC. All subgroups were assessed for PFS (primary endpoint), overall survival (OS), non-progression rate and objective response rate. Results: Overall, 256 patients provided samples for analysis. Considerable overlap was noted among biomarkers, except for EGFR and KRAS mutations, which are mutually exclusive. Other than EGFR mutations (p < 0.0001), no other biomarkers were significantly predictive of outcomes in a treatment-by-biomarker interaction test, although ERCC1 IHC-positive status was predictive of improved OS for the erlotinib arm versus placebo in EGFR wild-type patients (median 18.4 vs 9.5 months; hazard ratio [HR] HR = 0.32, 95% confidence intervals [CI] : 0.14-0.69, p = 0.0024). Conclusion: Activating EGFR mutations were predictive for improved treatment outcomes with a first-line intercalated regimen of chemotherapy and erlotinib in NSCLC. ERCC1 status may have some predictive value in EGFR wild-type disease, but requires further investigation.